HbA1c Levels Relate to the Severity of Atherosclerotic Lesions in Coronary Heart Disease Patients with Type 2 Diabetes Mellitus - Faridah Zulfa Rambe; Sheila Dhiene Putri (Universitas Muhammadiyah Sumatera Utara, 2026)
Abstract: Cardiovascular disease is one of the main causes of death in the world. In diabetes mellitus patients who experience hyperglycemia, the risk of coronary heart disease increases 2-4 times. Diabetes mellitus can be diagnosed using HbA1c examination. Coronary heart disease can be diagnosed using a coronary angiography examination, and the results are assessed using the vessel disease score. The design of this research is observational analytic with a cross-sectional approach. The research was conducted in October-December 2023 at RSU. Medan Hajj. The sample for this study was patients with coronary heart disease who had type 2 diabetes mellitus and underwent HbA1c examination and coronary angiography. Data analysis used the Mann-Whitney test. Based on data from RSU. Haji Medan obtained 23 samples, after 18 samples of multi-vessel disease were found with uncontrolled HbA1c levels, and then analysed with a result of 0.027 (p-value 0.05), which means there is a relationship between HbA1c levels and the severity of atherosclerotic lesions in disease patients. Coronary heart disease patients who have type 2 diabetes mellitus. There is a relationship between HbA1c levels and the severity of atherosclerotic lesions in coronary heart disease patients who have type 2 diabetes mellitus.